The Uses and Limitations of Law Students in Prison Legal Assistance Programs - John W. Oliver (Washington University Law Quarterly, 1969)
Address delivered to the National Council on Crime and Delinquency's Conference on the Role of Law Students in the Correctional Process, September 5, 1969, at the University of New Mexico School of Law, Albuquerque, New Mexico.
Keywords: Public legal service; Prisons and prisoners; Right to counsel